2020
DOI: 10.1186/s12879-020-05319-6
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological analysis of Acute Flaccid Paralysis (AFP) surveillance in Kenya, 2016 to 2018

Abstract: Background The poliovirus has been targeted for eradication since 1988. Kenya reported its last case of indigenous Wild Poliovirus (WPV) in 1984 but suffered from an outbreak of circulating Vaccine-derived Poliovirus type 2 (cVDPV2) in 2018. We aimed to describe Kenya’s polio surveillance performance 2016–2018 using WHO recommended polio surveillance standards. Methods Retrospective secondary data analysis was conducted using Kenyan AFP surveillance case-based database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 26 publications
6
10
0
Order By: Relevance
“…Our findings also showed that the majority of AFP cases (52%) were in age groups under 5 years. This is in line with findings from previous studies in Kenya, Ghana, Iran, Nigeria, and India [25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also showed that the majority of AFP cases (52%) were in age groups under 5 years. This is in line with findings from previous studies in Kenya, Ghana, Iran, Nigeria, and India [25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…Immunization coverage with three or more doses of OPV was 89.2 percent among AFP cases reported. This is in line with prior research (26,30,38). Bosch-Capblanch (33) conducted another investigation that yielded varying results.…”
Section: Afp Surveillance Performance Indicatorssupporting
confidence: 92%
“…When comparing males and females, our findings found a higher number of males (53.4%) compared to women (46.6%). This finding is consistent with research from Kenya, Ghana, Italy, and Ethiopia (26,27,30,31). It was clear that a large percentage of the reported cases had fever at the onset of paralysis, with paralysis asymmetrically and maximal progression within three days.…”
Section: Afp Surveillance Performance Indicatorssupporting
confidence: 89%
See 1 more Smart Citation
“…NPEVs are known to be related to AFP and may become more relevant as major causative agents of AFP at the polio eradication stage [ 12 , 13 , 14 , 15 , 16 ]. In this study, EV-A71 was the most frequently detected NPEV type and had a significant impact on the overall detection rate of NPEV in the AFP surveillance in Korea.…”
Section: Discussionmentioning
confidence: 99%